Probucol Nanostructured Lipid Carrier Ameliorates Elastase-induced Abdominal Aortic Aneurysm in Mice: Probucol nanostructured lipid carrier ameliorates abdominal aortic aneurysm - Yang, Mengting; Yuan, Yue; Liu, Yanhua; Chen, Cong; Cao, Yini; Qi, Rong (Iranian Journal of Pharmaceutical Sciences, 2019)
Probucol (PB) is a drug commonly used for the treatment of hyperlipidemia and atherosclerosis. In our previous study, we have proved that PB can ameliorate abdominal aortic aneurysm (AAA) induced by elastase in mice through its anti-inflammatory and anti-oxidative effect. In this study, the water solubility and oral absorption of PB were improved by encapsulating PB into nanostructured lipid carriers (PB-NLC), and the effects of NLC on the anti-AAA effects of PB were evaluated and compared to the PB free drug. AAA mouse model was constructed by incubating the mouse aorta with elastase. Mice in the drug-treated groups were given PB free drug or PB-NLC at a PB dose of either 10 mg/kg or 20 mg/kg daily, and mice in the model group were treated with saline. The arterial wall and the degradation grade of the elastic lamina were investigated by HE staining and aldehyde fuchsine staining of the aortic sections. Infiltration of macrophages and degree of inflammation were evaluated by immunohistochemical staining of CD68 and TNFα, respectively, in the aortic sections. In addition, the absorption improvement of PB by the NLC nano-formulation was evaluated through determining and comparing the steady-state plasma concentration of PB in the PB free drug or PB-NLC treated mice group. When treating the mice with AAA with an equal dose of PB, PB-NLC more significantly inhibited expansion of the abdominal aortas and maintained the integrity of the aortic walls, compared with the PB free drug. The NLC nano-formulation significantly increased the steady-state plasma concentration of PB. PB-NLC significantly increased the absorption and protective effects of PB against elastase-induced AAA in mice.